Manufacturing method for RTB sintered magnets
Patent Information
- Application Number
- JP2021049198
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-03-23
AI Technical Summary
【0011】 本開示の実施形態によると、磁気特性の低下を抑制しつつ金属溜りの発生を抑えることが可能なR-T-B系焼結磁石の製造方法を提供することができる。
Smart Images

Figure 0007631955000004 
Figure 0007631955000005 
Figure 0007631955000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an RTB based sintered magnet. [Background technology]
[0002] In recent years, there has been high demand for rare earth sintered magnets, and among them, RTB sintered magnets (R is a rare earth element and must contain at least one selected from the group consisting of Nd, Pr and Ce; T is at least one selected from the group consisting of Fe, Co, Al, Mn and Si and must contain Fe; B is boron) are known as the highest performance magnets, and are used in a variety of motors and home appliances, such as voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV, etc.), and motors for industrial equipment. RTB sintered magnets contribute to energy conservation and reduced environmental impact by making various motors smaller and lighter.
[0003] RTB sintered magnets are mainly 2 T 14 It is composed of a main phase made of B compounds and a grain boundary phase located at the grain boundary of this main phase. 2 T 14 B compounds are ferromagnetic materials with high saturation magnetization and anisotropic magnetic field, and form the basis of the properties of RTB sintered magnets.
[0004] At high temperatures, the coercive force H of RTB sintered magnets cJ (Hereafter, simply "H cJ This causes irreversible thermal demagnetization. Therefore, the RTB sintered magnets used in electric vehicle motors, in particular, have a high H cJ It is required that the applicant have:
[0005] In RTB sintered magnets, R 2 T 14 When a part of the light rare earth element RL (e.g., Nd or Pr) contained in R in the B compound is replaced with a heavy rare earth element RH (e.g., Tb or Dy), HcJ is known to improve. As the substitution amount of RH increases, H cJ improves. However, R 2 T 14 When RL in the R-T-B compound is replaced with RH, the H of the R-T-B sintered magnet cJ improves, while the residual magnetic flux density B r (hereinafter sometimes simply referred to as "B r ") decreases. In addition, since heavy rare earth elements are raw materials with a high resource risk, it is required to improve H without reducing or using their usage amount. cJ
[0006] Patent Document 1 discloses that by heat-treating and diffusing an alloy powder containing R1i-M1j (R1 is a rare earth element including Y and Sc, M1 is one or more selected from Al, Si, C, P, Ti, V, Cr, Mn, Ni, Cu, Zn, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, Hf, Ta, W, Pb, Bi, 15 < j ≦ 99, i is the balance) and containing 70% by volume or more of an intermetallic compound phase in a state where it exists on the surface of an R-T-B sintered magnet, H cJ is improved. Patent Document 2 discloses that by applying an adhesive to the surface of an R-T-B sintered magnet and attaching and heat-treating a powder of an alloy or compound of a heavy rare earth element which is at least one of Dy and Tb, H cJ is improved.
Prior Art Documents
Patent Documents
[0007]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0008] The present inventors have investigated a method of heat treating and diffusing RM alloy powder on the surface of an RTB sintered magnet as described in Patent Document 1, and have found that multiple protrusions with a height of 0.1 to 0.5 mm may occur on the surface of the sintered body after heat treatment. Further investigation has revealed that the protrusions are a mixture of a liquid phase produced by the melting of the RM alloy and a liquid phase produced from the RTB sintered magnet, and that the mixture of liquid phases is a metal pool that has risen due to solidification. The presence of metal pools reduces the processing accuracy in the subsequent process, which increases the number of processes for removing the metal pools, resulting in a problem of reduced productivity.
[0009] Therefore, an embodiment of the present disclosure provides a method for producing an RTB based sintered magnet that can suppress the occurrence of metal pools while suppressing the deterioration of magnetic properties. [Means for solving the problem]
[0010] In an exemplary embodiment, a method for producing an RTB based sintered magnet according to the present disclosure includes the steps of preparing an RTB based sintered magnet material (R is a rare earth element and must include at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, and must include Fe), and preparing an RM-Zr based alloy (R is a rare earth element and must include at least one selected from the group consisting of Nd, Pr, and Ce, and M is Al, Cu, Zn, Ga, Fe, Co, the RM-Zr alloy is a sintered RTB magnet material having a surface area of 700°C or more and a diffusion step of adhering the RM-Zr alloy to at least a portion of the surface of the RTB magnet material and heating the RM-Zr alloy to a temperature of 700°C or more and 1100°C or less in a vacuum or inert gas atmosphere, wherein the RM-Zr alloy has an R content of 70 mass% or more and 95 mass% or less, an M content of 4.5 mass% or more and 25 mass% or less, and a Zr content of 0.5 mass% or more and 5 mass% or less. In one embodiment, M of the RM-Zr alloy necessarily contains at least one of Cu and Ga, and the total content of Cu and Ga in M is 80% or more. Effect of the Invention
[0011] According to the embodiments of the present disclosure, it is possible to provide a method for producing an RTB based sintered magnet that can suppress the occurrence of metal pools while suppressing the deterioration of magnetic properties. [Brief description of the drawings]
[0012] [Figure 1A] FIG. 2 is an enlarged schematic cross-sectional view of a portion of an RTB based sintered magnet. [Figure 1B] 1B is a cross-sectional view showing a further enlarged schematic view of the dashed rectangular region in FIG. 1A. [Diagram 2] 1 is a flowchart showing an example of steps in a method for producing an RTB based sintered magnet according to the present disclosure. [Diagram 3] 1 is a photograph showing the appearance of Sample No. 1-1. [Figure 4] 1 is a photograph showing the appearance of Sample No. 1-2. [Diagram 5] 1 is a photograph showing the appearance of Sample No. 1-3. [Figure 6] 1 is a photograph showing the appearance of Sample No. 1-4. [Figure 7] 1 is a photograph showing the appearance of Sample No. 1-5. [Figure 8] 1 is a photograph showing the appearance of Sample No. 1-6. [Figure 9] 1 is a photograph showing the appearance of Sample No. 1-7. [Figure 10] 1 is a photograph showing the appearance of Sample No. 1-8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] First, the basic structure of the RTB based sintered magnet according to the present disclosure will be described. The RTB based sintered magnet has a structure in which powder particles of raw alloy are bonded together by sintering, and is mainly composed of R 2 T 14It is composed of a main phase made of B compound particles and a grain boundary phase located at the grain boundaries of this main phase.
[0014] FIG. 1A is a cross-sectional view showing an enlarged schematic view of a portion of an RTB sintered magnet, and FIG. 1B is a cross-sectional view showing an enlarged schematic view of the dashed rectangular region in FIG. 1A. In FIG. 1A, an arrow of 5 μm in length is shown as an example for reference, showing the reference length of the size. As shown in FIG. 1A and FIG. 1B, an RTB sintered magnet is mainly composed of R 2 T 14 The grain boundary phase 14 is composed of a main phase 12 made of a B compound and a grain boundary phase 14 located at the grain boundary portion of the main phase 12. As shown in FIG. 1B, the grain boundary phase 14 is composed of two R 2 T 14 The two-particle grain boundary phase 14a in which B compound particles (grains) are adjacent, and the three R 2 T 14 The grain boundary triple junction 14b includes adjacent B compound particles. The typical main phase crystal grain size is 3 μm or more and 10 μm or less in terms of the average circle equivalent diameter of the magnet cross section. 2 T 14 B compounds are ferromagnetic materials with high saturation magnetization and anisotropic magnetic field. Therefore, in RTB sintered magnets, the main phase12, R 2 T 14 By increasing the proportion of B compounds, r It can improve R 2 T 14 In order to increase the ratio of B compounds, the amounts of R, T, and B in the raw alloy should be adjusted to R 2 T 14 It is sufficient to approach the stoichiometric ratio of the B compound (amount of R:amount of T:amount of B = 2:14:1).
[0015] In addition, the main phase R 2 T 14It is known that by substituting a part of the R in B compounds with heavy rare earth elements such as Dy, Tb, and Ho, the saturation magnetization can be reduced while the anisotropy field of the main phase can be increased. In particular, the outer shell of the main phase that contacts the two-particle grain boundary phase is likely to be the starting point of magnetization reversal, so the heavy rare earth diffusion technology, which can preferentially substitute heavy rare earth elements in the outer shell of the main phase, can efficiently achieve high H while suppressing the decrease in saturation magnetization. cJ is obtained.
[0016] On the other hand, by controlling the magnetism of the two-grain grain boundary phase 14a, a high H cJ Specifically, by lowering the concentration of magnetic elements (Fe, Co, Ni, etc.) in the two-particle grain boundary phase, the two-particle grain boundary phase becomes closer to non-magnetic, weakening the magnetic coupling between the main phases and suppressing magnetization reversal.
[0017] In the manufacturing method of the RTB sintered magnet according to the present disclosure, R and M contained in the RM-Zr alloy are diffused from the surface of the RTB sintered magnet material through the grain boundaries into the inside of the magnet material. As a result of research, the present inventors have found that the occurrence of metal pools can be suppressed by further including Zr in a specific range in the alloy powder in which R and M are diffused. Furthermore, it has been found that Zr is hardly diffused into the inside of the RTB sintered magnet after diffusion. This makes it possible to suppress the occurrence of metal pools while suppressing the deterioration of magnetic properties. This is believed to be because by including Zr in a specific range in the alloy powder to be diffused, it is possible to increase the melting point of the RM-Zr alloy without diffusing Zr into the inside of the RTB sintered magnet. This makes it possible to suppress the occurrence of metal pools while suppressing the deterioration of magnetic properties by reducing the amount of liquid phase generated from the RM-Zr alloy during diffusion.
[0018] The method for producing an RTB based sintered magnet according to the present disclosure includes step S10 of preparing an RTB based sintered magnet material and step S20 of preparing an RM-Zr based alloy, as shown in Fig. 2. The order of step S10 of preparing the RTB based sintered magnet material and step S20 of preparing the RM-Zr based alloy may be arbitrary. As shown in FIG. 2, the method for producing an RTB based sintered magnet according to the present disclosure further includes a diffusion step S30 in which an RM-Zr based alloy is adhered to at least a portion of the surface of the RTB based sintered magnet material, and then heated at a temperature of 700° C. or higher and 1100° C. or lower in a vacuum or inert gas atmosphere.
[0019] In this disclosure, the RTB based sintered magnet before and during the diffusion process is referred to as the "RTB based sintered magnet material", and the RTB based sintered magnet after the diffusion process is simply referred to as the "RTB based sintered magnet".
[0020] (Preparation of RTB sintered magnet material) In the RTB sintered magnet material, R is a rare earth element that necessarily contains at least one selected from the group consisting of Nd, Pr, and Ce, and the content of R is, for example, 27 mass% to 35 mass% of the entire RTB sintered magnet material. T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, T necessarily contains Fe, and the content of Fe in the entire T is 80 mass% or more. If R is less than 27 mass%, the liquid phase is not sufficiently generated during the sintering process, and it may be difficult to sufficiently densify the sintered body. On the other hand, if R exceeds 35 mass%, grain growth occurs during sintering, and H cJ R is preferably 28 mass% or more and 33 mass% or less.
[0021] The RTB based sintered magnet material has, for example, the following composition range. R: 27-35 mass%, B: 0.80 to 1.20 mass%, Ga: 0 to 1.0 mass%, X: 0 to 2 mass% (X is at least one of Cu, Nb, and Al); T: Contains 60 mass% or more.
[0022] Preferably, in the RTB based sintered magnet material, the molar ratio of T to B, [T] / [B], is greater than 14.0 and not greater than 15.0.cJ In the present disclosure, [T] / [B] is the ratio of [T], which is the sum of the analytical values (mass%) of each element constituting T (at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, where T necessarily contains Fe and the content of Fe in the entire T is 80 mass% or more) divided by the atomic weight of each element, to [B], which is the analytical value (mass%) of B divided by the atomic weight of B. The condition that the molar ratio [T] / [B] exceeds 14.0 is satisfied when the main phase (R 2 T 14 It is more preferable that the molar ratio [T] / [B] is 14.3 or more and 15.0 or less. cJ The B content is preferably 0.9 mass % or more and less than 1.0 mass % of the entire RTB sintered body.
[0023] The RTB sintered magnet material can be prepared by a general manufacturing method for RTB sintered magnets, such as Nd-Fe-B sintered magnets. For example, a raw material alloy produced by strip casting or the like is milled into powder with a particle size D 50 The powder can be prepared by crushing the powder to a size of 2.0 μm to 3.5 μm, molding the powder in a magnetic field, and sintering the powder at a temperature of 900° C. to 1100° C. to produce a sintered body. 50 By grinding to 2.0μm to 3.5μm, a high B r and high H cJ Preferably, the particle size D 50 The thickness is 2.5μm or more and 3.3μm or less. It is possible to reduce valuable RH while suppressing deterioration of productivity and achieve a higher B r and high H cJ It is possible to obtain the particle size D 50 is the particle size at which the cumulative particle size distribution (volume basis) from the small diameter side becomes 50% in the particle size distribution obtained by the laser diffraction method using the air flow dispersion method. 50can be measured, for example, using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec under the conditions of dispersion pressure: 4 bar, measurement range: R2, and measurement mode: HRLD.
[0024] (Preparing RM-Zr alloy) In the RM-Zr alloy, R is a rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr, and Ce. The content of R is 70 mass% or more and 95 mass% or less of the entire RM-Zr alloy. M is at least one selected from the group consisting of Al, Cu, Zn, Ga, Fe, Co, and Ni. The content of M is 4.5 mass% or more and 25 mass% or less of the entire RM-Zr alloy. The content of Zr is 0.5 mass% or more and 5 mass% or less of the entire RM-Zr alloy. Typical examples of RM-Zr alloys are TbNdPrCuZr alloy, TbNdCePrCuZr alloy, TbNdGaZr alloy, TbNdPrGaCuZr alloy, etc. In addition to the above elements, elements such as inevitable impurities such as Mn, O, C, and N may be contained in small amounts.
[0025] When R is less than 70 mass%, H cJ If the R content exceeds 95 mass%, the alloy powder in the manufacturing process of the RM-Zr alloy becomes very active. As a result, the alloy powder may be significantly oxidized or ignite. The R content is preferably 80 mass% or more and 90 mass% or less of the entire RM-Zr alloy. cJ can be obtained. In addition, the method for producing an RTB based sintered magnet according to the present disclosure can reduce the amount of heavy rare earth elements (Tb, Dy, etc.) used while achieving high B r and high H cJ Therefore, the content of the heavy rare earth element is preferably 10 mass % or more and 20 mass % or less of the entire RM-Zr-based alloy, and more preferably, the RM-Zr-based alloy does not contain any heavy rare earth element.
[0026] If M is less than 4.5 mass%, it becomes difficult for R and M to be incorporated into the two-particle grain boundary phase, and H cJ If it exceeds 25 mass%, the R content decreases and H cJ The content of M is preferably 7 mass% or more and 15 mass% or less of the entire RM-Zr alloy. cJ It is preferable that M contains at least one of Cu and Ga, and more preferable that M contains both Cu and Ga. The total content of Cu and Ga in M is preferably 80% or more. By containing Cu and Ga, a higher H cJ can be obtained.
[0027] If Zr is less than 0.5 mass%, it may not be possible to prevent the occurrence of metal accumulation in the RTB sintered magnet after diffusion. If it exceeds 5 mass%, H cJ The occurrence of metal pools can be suppressed while suppressing the deterioration of magnetic properties by including Zr in a specific range in the alloy powder in which R and M are diffused. The Zr content is preferably 0.8 mass% or more and 4 mass% or less, and more preferably 0.8 mass% or more and 2 mass% or less. The occurrence of metal pools can be suppressed while suppressing the deterioration of magnetic properties.
[0028] The method for producing the RM-Zr alloy is not particularly limited. It may be produced by roll quenching or casting. These alloys may be pulverized to produce alloy powder. It may also be produced by known atomization methods such as centrifugal atomization, rotating electrode method, gas atomization, and plasma atomization.
[0029] (Diffusion process) The RM-Zr alloy prepared as described above is applied to at least a portion of the surface of the RTB sintered magnet material, and a diffusion step is performed in which the material is heated in a vacuum or inert gas atmosphere at a temperature of 700°C to 1100°C. As a result, a liquid phase containing R and M is generated from the RM-Zr alloy, and the liquid phase is diffused from the surface of the sintered magnet material to the inside via the grain boundaries in the RTB sintered magnet material. The amount of RM-Zr alloy attached to the RTB sintered magnet material in the diffusion step is preferably 1 mass% to 5 mass%, and more preferably 1.5 mass% to 3 mass%. Higher H cJ can be obtained.
[0030] If the heating temperature in the diffusion process is less than 700°C, the amount of liquid phase containing R and M is too small, resulting in high H cJ On the other hand, if the temperature exceeds 1100℃, H cJ The heating temperature in the diffusion step is preferably 800°C or higher and 1000°C or lower. cJ It is also preferable to cool the RTB sintered magnet that has been subjected to the diffusion step (700°C or more and 1100°C or less) from the temperature at which the diffusion step was performed to 300°C at a cooling rate of 15°C / min or more. cJ can be obtained.
[0031] The diffusion step can be performed by disposing an RM-Zr alloy of any shape on the surface of the RTB sintered magnet material and using a known heat treatment device. For example, the surface of the RTB sintered magnet material can be covered with a powder layer of the RM-Zr alloy and then the diffusion step can be performed. For example, a coating step of coating an adhesive on the surface to be coated and a step of attaching the RM-Zr alloy to the area coated with the adhesive may be performed. Examples of adhesives include PVA (polyvinyl alcohol), PVB (polyvinyl butyral), and PVP (polyvinylpyrrolidone). When the adhesive is a water-based adhesive, the RTB sintered magnet material may be preheated before coating. The purpose of the preheating is to remove excess solvent to control the adhesive strength and to attach the adhesive uniformly. The heating temperature is preferably 60 to 200°C. In the case of a highly volatile organic solvent-based adhesive, this step may be omitted. In addition, for example, a slurry in which the RM-Zr alloy is dispersed in a dispersion medium may be applied to the surface of the RTB sintered magnet material, and then the dispersion medium may be evaporated to adhere the RM-Zr alloy to the RTB sintered magnet material. Examples of the dispersion medium include alcohol (such as ethanol), aldehydes, and ketones.
[0032] (Heat treatment process) As shown in Fig. 2, the RTB based sintered magnet that has been subjected to the diffusion step is preferably subjected to a heat treatment S40 in a vacuum or inert gas atmosphere at a temperature of 400°C to 750°C, both inclusive, and lower than the temperature used in the diffusion step. cJ can be obtained. EXAMPLES
[0033] The present invention will be described in more detail with reference to examples, but the present invention is not limited thereto.
[0034] Experimental Example 1 [Preparing RT-B based sintered magnet material] Each element was weighed to obtain the composition of the RTB sintered magnet material shown in No. 1 of Table 1, and a raw alloy was produced by strip casting. Each alloy obtained was coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powder. The coarsely pulverized powder was then finely pulverized by a jet mill. The fine pulverization resulted in a particle size D 50 A fine powder with a particle size of 4.2 μm was obtained. The obtained finely pulverized powder was molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other. The obtained green body was sintered in a vacuum for 4 hours (a temperature was selected that would sufficiently cause densification by sintering) and then rapidly cooled to obtain an RTB sintered magnet material. The obtained RTB sintered magnet material had a density of 7.5 Mg / m 3 That was all. To determine the composition of the resulting RTB sintered magnet material, the contents of Nd, Pr, Dy, B, Co, Al, Cu, Ga, and Tb were measured by inductively coupled plasma optical emission spectroscopy (ICP-OES). The analysis results are shown in Table 1.
[0035] [Table 1]
[0036] [Preparing RM-Zr alloy] Each element was weighed so as to obtain the alloy compositions shown in No. 1-A to 1-G in Table 2, and the raw materials were melted and ribbon- or flake-shaped alloys were obtained by single-roll ultra-quenching. The compositions of the obtained alloys (RM-Zr alloys and comparative alloys) are shown in Table 2. Each component in Table 2 was measured using high-frequency inductively coupled plasma atomic emission spectrometry.
[0037] [Table 2]
[0038] [Diffusion process] The RTB sintered magnet material No. 1 in Table 1 was cut and machined into a rectangular parallelepiped of 45 mm x 52 mm x 4 mm. PVA was applied as an adhesive to the entire surface of the processed RTB sintered magnet material by dipping. Next, an alloy was attached to the entire surface of the RTB sintered magnet material coated with the adhesive under the conditions shown in Table 3. The amount of alloy attached was adjusted by crushing the alloy in an argon atmosphere using a mortar, passing it through several types of sieves with openings of 45 to 1000 μm, and using alloys with different particle sizes. Then, using a vacuum heat treatment furnace, the alloy and the RTB sintered magnet material were heated under the conditions shown in Table 3 in a reduced pressure argon atmosphere controlled at 100 Pa, and then cooled.
[0039] [Heat treatment process] The RTB based sintered magnet material heated in the diffusion step was subjected to a heat treatment at 500°C in a vacuum heat treatment furnace in reduced pressure argon controlled at 100 Pa. The heating temperatures of the RM-Zr based alloy and the RTB based sintered magnet material in the diffusion step, and the heating temperature of the RTB based sintered magnet in the step of carrying out the heat treatment after the diffusion step, were each measured using a thermocouple.
[0040] [Sample evaluation] After the heat treatment, each sample was machined on its entire surface using a surface grinder to obtain rectangular parallelepiped samples (RTB-based sintered magnets) measuring 7.0 mm x 7.0 mm x 7.0 mm. The residual magnetic flux density B r and coercive force H cJ was measured. The results are shown in Table 3. The appearance of each sample No. after the diffusion step is shown in Figs. 3 to 10. Fig. 3 is a photograph showing the appearance of No. 1-1, Fig. 4 is a photograph showing the appearance of No. 1-2, Fig. 5 is a photograph showing the appearance of No. 1-3, Fig. 6 is a photograph showing the appearance of No. 1-4, Fig. 7 is a photograph showing the appearance of No. 1-5, Fig. 8 is a photograph showing the appearance of No. 1-6, Fig. 9 is a photograph showing the appearance of No. 1-7, and Fig. 10 is a photograph showing the appearance of No. 1-8. The number of metal puddles that occurred on the surface of the RTB sintered magnets in Nos. 1-1 to 1-8 was evaluated. The metal puddles were convex portions of about 0.5 mm or more. Nine metal puddles occurred in No. 1-1, which is a comparative example. On the other hand, in Nos. 1-2 to 1-4, which are examples of the present invention, r is 1.450T or more and H cJ The comparative example No. 1-5 had high B r and high H cJ Although more than 30 metal pools were observed, the comparative example No. 1-6 did not show any metal pools, but the Br value was decreased. The comparative examples No. 1-7 and 1-8 showed high B values. r and high H cJ However, seven and two metal pools were observed, respectively.
[0041] [Table 3]
Claims
[Claim 1] preparing an R-T-B based sintered magnet material (R is a rare earth element and must contain at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, and must contain Fe); preparing an R-M-Zr alloy (R is a rare earth element, and must contain at least one selected from the group consisting of Nd, Pr, and Ce, M is at least one selected from the group consisting of Al, Cu, Zn, Ga, Fe, Co, and Ni, and must contain at least one of Cu and Ga, and the total content of Cu and Ga in M is 80% or more); a diffusion step of adhering the R-M-Zr based alloy to at least a part of the surface of the R-T-B based sintered magnet material, and heating the resulting material at a temperature of 700° C. or higher and 1100° C. or lower in a vacuum or inert gas atmosphere; The method for producing an R-T-B based sintered magnet, wherein the R content in the R-M-Zr based alloy is 70 mass% or more and 95 mass% or less, the M content is 4.5 mass% or more and 25 mass% or less, and the Zr content is 0.5 mass% or more and 5 mass% or less.
Citation Information
Patent Citations
Rare earth permanent magnet and manufacturing method
JP2008235343A
Rare earth permanent magnet and method of manufacturing the same
JP2008263179A
Method for preparing rare earth magnet, and rare earth magnet
JP2011014668A
Rare earth permanent magnet and method for producing the same
JP2012248828A
Process for production of r-t-b based sintered magnets and r-t-b based sintered magnets
WO2011007758A1